"Source" or "Activity" What is the Level of Issue in a Criminal Trial?. Issue 2 (1st April 2019) - Jackson, Graham; Biedermann, Alex
Abstract : With DNA evidence, so-called match probabilities are potentially misleading if they are used to answer questions that they are not designed to answer. Are we interested in who is the source of the detected DNA, or are we interested in whether a particular alleged activity occurred? Graham Jackson and Alex Biedermann explore this issue.